A walk in the rainforest - Pratt, Kristin Joy. (Nevada City, CA : Dawn Publications, 1992)
Follows the travels of XYZ, the ant, as he explores the lush vegetation and unusual animals that make their home in the rain forest.
Elem. School Library Collection
5.9
3-6
Keywords: Rain forest ecology -- Juvenile literature; Rain forest animals -- Juvenile literature; Rain forest plants -- Juvenile literature; Endangered species -- Juvenile literature; Rain forest animals; Rain forest plants; Rain forest ecology; Ecology; Endangered species; Alphabet; Rain forest animals; Rain forest plants; Rain forest ecology; Alphabet